FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAHAN KABUPATEN OKI - Dona, Dwi Zarima; Sari, Kartika Rachma; Armaini, Rosy (Jurnal Riset Terapan Akuntansi, 2024)
This study aims to empirically determine the influence of the implementation of government accounting standards, internal control systems, utilization of information technology, and human resource competence on the quality of financial reporting. The type of data used in this study is quantitative data obtained through questionnaires. The population in this study consists of Regional Apparatus Organizations (OPD) with a sampling method using saturated sampling. Data analysis was conducted using SPSS version 26. The statistical method used in this study is multiple linear regression. The results indicate that the implementation of government accounting standards, internal control systems, utilization of information technology, and human resource competence partially have a positive and significant impact on the quality of financial reporting of the Ogan Komering Ilir Regency Government. The implementation of government accounting standards, internal control systems, utilization of information technology, and human resource competence simultaneously also have a positive and significant impact on the quality of financial reporting of the Ogan Komering Ilir Regency Government.Keywords: Financial Reporting, SAP, SPI, PTI, Human Resource Competence